A Review of the Effectiveness of Homoeoprophylaxis: SARS-CoV-2 Compared to Pre-COVID-19 Infectious Diseases - Golden, Isaac; Bracho, Gustavo (Homœopathic Links, 2023)
From Hahnemann's use in 1799 of Belladonna 30 to prevent scarlet fever, to the prevention of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in 2023, appropriate potencies of similarly 'similar' remedies have been used to prevent targeted infectious diseases. This is known to many as homeoprophylaxis (HP) or 'similar prevention.' Data from recent surveys suggest that the effectiveness of HP remedies against SARS-CoV-2 is lower compared to other infectious diseases. This review examines relevant evidence and suggests possible explanations for the emerging difference and ways to improve HP effectiveness. Evidence of HP's effectiveness against a range of infectious diseases from 1974 to 2014 is compared with evidence of HP's effectiveness against SARS-CoV-2 collected from 2020 to 2022. A summary of the evidence, describing the use of over 247,000,000 doses of HP medicines against various infectious diseases, suggests an average effectiveness of around 88%. Another summary of the evidence, describing the use of HP by several authors in 2020, 2021, and 2022 against SARS-CoV-2, shows a range of effectiveness around 70%. The reasons for apparent differences in HP effectiveness between 'traditional' infectious diseases and SARS-CoV-2 are discussed. It is suggested that these differences could have been expected, particularly due to the quality of most nosodes against SARS-CoV-2. The value of HP in comparison to coronavirus disease 2019 vaccines is also discussed, and conclusions are drawn. Appropriate HP against SARS-CoV-2 offers an option that appears to be at least as effective as vaccination, without any risk of toxic damage, but there is room for improvement.
Keywords: homoeoprophylaxis; immunisation; effectiveness; infectious diseases; SARS-CoV-2